Ukraina – hva bør vites? - Jørn Holm-Hansen; Marthe Handå Myhre; Aadne Aasland (Nordisk Østforum)
This article serves as an introduction to Nordisk Østforum’s thematic series of articles on Ukraine and focuses on three aspects: nation-building, demographics and political power relations. All three of these aspects of Ukraine’s development are undergoing rapid change, and the need for knowledge is great. After presenting the current status, the article identifies knowledge gaps that most urgently need to be filled, including those related to nation-building and societal cohesion, the effects of the war and the refugee situation on cleavages in Ukrainian politics, the relationship between the politics of Ukraine and of recipient countries regarding Ukrainian refugees and their return, political and economic power centres should “de-oligarchisation” succeed, and the role of civil society in Ukraine in a time of reconstruction assistance.